Alex the ant goes to the beach - Dickey, Eric Wayne, 1967-; Paccia, Abbey (Portland, OR : Craigmore Creations, 2014)
When Alex accompanies older ants to the beach on his first trip outside of Underwood, he enjoys playing but also demonstrates that he will one day be a great scout for Queen Aziza when he alerts the work crew to danger.
3.6
K-3
AD820L
Keywords: Ants -- Fiction; Ants -- Fiction; Beaches -- Fiction